1999
DOI: 10.1023/a:1002445219981
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The micropig is viewed by many as one of the best animal models of human system physiology. The purpose of this study was to develop a simple, rapid and reliable method to record clinical electroretinograms from conscious adult Yucatan micropigs. Photopic ERGs were recorded from 18 conscious animals following a 3-h period of preadaptation to a moderate photopic environment. Rectal temperature and blood pressure were monitored throughout the experiment. In order to test the reproducibility of our procedure, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…Previous studies of ERG using normal pig showed the a-wave implicit time (16.6 ms) in rod-cone response, b-wave implicit time (41.8–47.4 ms) in rod-cone response, a-wave implicit time (12.7–16.7 ms) in maximal rod-cone response, b-wave implicit time (36.0–45.0 ms) in maximal rod-cone response, a-wave implicit time (8.37–13.4 ms) in cone response, and b-wave implicit time (29.6–33.5 ms) in cone response. 33 , 34 , 59 , 60 The b-wave amplitude of 10.0 ERG in our study showed a smaller amplitude than that of 3.0 ERG.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous studies of ERG using normal pig showed the a-wave implicit time (16.6 ms) in rod-cone response, b-wave implicit time (41.8–47.4 ms) in rod-cone response, a-wave implicit time (12.7–16.7 ms) in maximal rod-cone response, b-wave implicit time (36.0–45.0 ms) in maximal rod-cone response, a-wave implicit time (8.37–13.4 ms) in cone response, and b-wave implicit time (29.6–33.5 ms) in cone response. 33 , 34 , 59 , 60 The b-wave amplitude of 10.0 ERG in our study showed a smaller amplitude than that of 3.0 ERG.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous studies also exist regarding ERG recordings from conscious animals such as yucatan micropigs [26], rats [32], and dogs [28]. The studies revealed that recording artifacts from blinks, eye, and head movements are frequent in the conscious dogs, which necessitate the averaging of the multiple responses in order to reduce the artifcact effect [17].…”
Section: Introductionmentioning
confidence: 99%